Hydroxyl acrylic resin and preparation method thereof, paint and coating
By adjusting the combination and preparation process of methyl side chain and benzene ring structural monomer in acrylic resin, the problem of high viscosity of high solid content resin is solved, low viscosity characteristics, excellent construction performance and corrosion resistance are achieved, and suitable for steel Structural anticorrosion coating.
Patent Information
- Application Number
- CN202411495517.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing high-solid content hydroxyacrylic resin has a high viscosity, which leads to the need to add organic solvent diluents when used in steel structure anticorrosion coatings, which increases VOC emissions and costs, and limits its application development.
By adjusting the combination of acrylate monomers containing methyl side chains and benzene ring-containing hard monomers, the preparation process of continuous supplementation initiator is adopted to improve the monomer conversion and viscosity control of the resin, and a high solid content is prepared by preparing Low viscosity hydroxyacrylic resin.
The high solids content and low viscosity characteristics of the resin are achieved, the construction performance and weatherability of the coating are improved, the acid and alkali resistance are resisted, and the VOC emissions and costs are reduced.
Smart Images

Figure BDA0005101273270000081 
Figure BDA0005101273270000091 
Figure BDA0005101273270000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of acrylic resins, and in particular to a high-solid, low-viscosity hydroxy acrylic resin for steel structure anti-corrosion coatings and a preparation method thereof, as well as a coating comprising the same and a coating formed by the coating. Background Art
[0002] In recent years, with the continuous improvement of environmental protection policy requirements, the international market has adopted more stringent restrictions on the emission of VOCs from coatings. At present, low-pollution organic solvent coating products mainly include water-based coatings, powder coatings, radiation-cured coatings and high-solid coatings. As a new type of high-solid coating base material, high-solid and low-viscosity hydroxyl acrylic resin has attracted much attention in recent years. High-solid resins have a low organic solvent content, which can reduce the emission of VOCs from products. They also have the advantages of excellent water resistance, chemical corrosion resistance, good adhesion and excellent optical transparency. They can also be used in a variety of coating scenarios, such as automotive coatings, architectural coatings, and surface coatings for electronic products. However, the viscosity of the high-solid content hydroxyl acrylic resins commonly found on the market is usually high. In order to ensure that the viscosity of the coating system is suitable for normal construction, an additional organic solvent diluent must be added in actual use, which will further increase VOC emissions and increase the overall cost of the coating. This greatly limits its application and development in anti-corrosion coatings for steel structures. Therefore, it is necessary to invent and design a hydroxyl acrylic resin that takes into account both high solid content and low viscosity characteristics to solve the above problems. Summary of the invention
[0003] The following is a summary of the subject matter described in detail herein. This summary is not intended to limit the scope of the claims.
[0004] Based on the problems raised in the background technology, this application provides a hydroxy acrylic resin with high solid content and low viscosity characteristics and a preparation experimental process, and adjusts different combinations of acrylic ester monomers containing methyl side chains and hard monomers containing benzene ring structures. In terms of preparation process, by continuously adding a specific initiator and continuing the reaction at a selected temperature, the monomer conversion rate of the resin can reach 99%. The solid content of the preferably prepared hydroxy acrylic resin varnish is about 70%, and the viscosity of the resin is controlled within 1500-3000mPa·s. It has high hardness and adhesion, and also has excellent weather resistance and acid and alkali resistance.
[0005] To achieve the above objectives, this application adopts the following technical solutions:
[0006] The first aspect of the present application provides a hydroxy acrylic resin, wherein the raw materials of the hydroxy acrylic resin include: (meth) acrylate monomer, acrylic acid, initiator and organic solvent, and aromatic vinyl monomer.
[0007] In an exemplary embodiment, the monomer conversion rate of the hydroxy acrylic resin is 99%, the solid content is 66.6%-66.8%, and the viscosity of the resin is controlled at 1500-3000 mPa·s.
[0008] In an exemplary embodiment, the (meth)acrylate monomer is one or a mixture of methyl methacrylate, butyl methacrylate, butyl acrylate, hydroxyethyl acrylate, methyl acrylate, and propyl acrylate;
[0009] Preferably, the (meth)acrylate monomer is one or a mixture of methyl methacrylate, butyl methacrylate, butyl acrylate, and hydroxyethyl acrylate.
[0010] In an exemplary embodiment, the aromatic vinyl monomer is styrene.
[0011] In an exemplary embodiment, the raw materials of the hydroxylated acrylic resin include, by mass percentage: 4%-15% of methyl methacrylate, 3%-12% of butyl methacrylate, 15%-25% of butyl acrylate, 8%-15% of hydroxyethyl acrylate, 15%-25% of styrene, 0.3%-1.0% of acrylic acid, 0.1%-2.5% of initiator, and 21%-45% of organic solvent.
[0012] In an exemplary embodiment, the raw materials of the hydroxylated acrylic resin are composed, by mass percentage, of 4%-15% methyl methacrylate, 3%-12% butyl methacrylate, 15%-25% butyl acrylate, 8%-15% hydroxyethyl acrylate, 15%-25% styrene, 0.3%-1.0% acrylic acid, 0.1%-2.5% initiator, and 21%-45% organic solvent.
[0013] In an exemplary embodiment, the organic solvent is one or a mixture of xylene, toluene, butyl acetate, ethyl acetate, butanone and pentanone;
[0014] Preferably, the organic solvent is a mixture of xylene and butyl acetate.
[0015] In an exemplary embodiment, the raw materials of the hydroxylated acrylic resin include, by mass percentage: 4%-15% of methyl methacrylate, 3%-12% of butyl methacrylate, 15%-25% of butyl acrylate, 8%-15% of hydroxyethyl acrylate, 15%-25% of styrene, 0.3%-1.0% of acrylic acid, 0.1%-2.5% of initiator, 20%-30% of xylene, and 1%-15% of butyl acetate.
[0016] In an exemplary embodiment, the raw materials of the hydroxylated acrylic resin are composed, by mass percentage, of 4%-15% methyl methacrylate, 3%-12% butyl methacrylate, 15%-25% butyl acrylate, 8%-15% hydroxyethyl acrylate, 15%-25% styrene, 0.3%-1.0% acrylic acid, 0.1%-2.5% initiator, 20%-30% xylene, and 1%-15% butyl acetate.
[0017] In an exemplary embodiment, in the hydroxy acrylic resin, the mass ratio of the methyl side chain acrylic monomer (methyl methacrylate, butyl methacrylate) to the benzene ring structure hard monomer (styrene) is 1:1.4-2.8.
[0018] In an exemplary embodiment, the initiator is one of azobisisobutyl cyanide, azobisisoheptyl cyanide, dibenzoyl peroxide, cumene hydroperoxide, potassium persulfate, and ammonium persulfate. The half-life of the initiator at 70° C. is 8-12 hours. The higher the temperature, the shorter the half-life of the initiator used, the more free radical active sites generated by decomposition, and the lower the viscosity of the generated resin.
[0019] In an exemplary embodiment, the initiator is dibenzoyl peroxide.
[0020] In an exemplary embodiment, the raw materials of the hydroxy acrylic resin are composed of the following by mass percentage: 6.2% methyl methacrylate, 5% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 21.3% styrene, 0.8% acrylic acid, 2.5% initiator, 21.8% xylene, and 11% butyl acetate;
[0021] Among them, in the hydroxy acrylic resin, the mass ratio of the acrylic monomer containing a methyl side chain to the hard monomer containing a benzene ring structure is 1:1.9.
[0022] In an exemplary embodiment, the raw materials of the hydroxy acrylic resin are composed of the following by mass percentage: 5.4% methyl methacrylate, 4.5% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 22.7% styrene, 0.8% acrylic acid, 2.5% dibenzoyl peroxide, 21.8% xylene, and 11% butyl acetate;
[0023] Among them, in the hydroxy acrylic resin, the mass ratio of the acrylic monomer containing a methyl side chain to the hard monomer containing a benzene ring structure is 1:2.3.
[0024] In an exemplary embodiment, the raw materials of the hydroxy acrylic resin are composed of the following by mass percentage: 4.8% methyl methacrylate, 4% butyl methacrylate, 20% butyl acrylate, 11.4% hydroxyethyl acrylate, 23.8% styrene, 0.8% acrylic acid, 2.5% dibenzoyl peroxide, 21.8% xylene, and 11% butyl acetate;
[0025] Among them, in the hydroxy acrylic resin, the mass ratio of the acrylic monomer containing a methyl side chain to the hard monomer containing a benzene ring structure is 1:2.7.
[0026] The second aspect of the present application provides a method for preparing the above-mentioned hydroxy acrylic resin, comprising the following steps:
[0027] 1) According to the proportion, methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and part of the initiator are sucked into a dropping tank and stirred to obtain a mixture;
[0028] 2) adding part of xylene and all of butyl acetate to the reactor as a base and heating it, dripping the mixture in the dropping tank into the reactor, and maintaining copolymerization after the dripping is completed;
[0029] 3) Add the remaining xylene and initiator, keep warm and then cool down to discharge the material.
[0030] In an exemplary embodiment, step 1) comprises: according to the ratio, methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, and acrylic acid are pumped into a dropping tank, a portion of the initiator is weighed and added into the dropping tank, and stirring is started until the mixture is uniformly dissolved to obtain the mixture;
[0031] Optionally, the initiator is added in an amount of 80%.
[0032] In an exemplary embodiment, step 2) comprises: adding 80% of xylene and all of butyl acetate into a reactor to form a bottom and heating it, dripping the mixture in the dripping tank into the reactor, and maintaining copolymerization for 1 hour after the dripping is completed;
[0033] Optionally, 80% of the amount of xylene and the entire amount of butyl acetate are added to the reactor apparatus as a bottom, and the temperature is raised to 124±2°C within 1.5 hours and maintained for 10 minutes;
[0034] Optionally, at 124±2° C. and without reflux, the mixture in the dropping tank is dripped into the reaction kettle within 2-2.5 hours, and the copolymerization is maintained for 1 hour after the dripping is completed.
[0035] In an exemplary embodiment, step 3) includes: at 124±2°C, adding the remaining xylene and initiator mixture to the reactor within 5-10 minutes, maintaining copolymerization for 2 hours, cooling the reactor to 80°C and discharging the material to obtain the hydroxy acrylic resin.
[0036] The third aspect of the present application provides a hydroxy acrylic resin prepared by the above-mentioned preparation method of the hydroxy acrylic resin.
[0037] A fourth aspect of the present application provides a coating, wherein the raw materials of the coating include the above-mentioned hydroxy acrylic resin.
[0038] A fifth aspect of the present application provides a coating formed by the above-mentioned coating.
[0039] Compared with the prior art, this application has the following beneficial effects:
[0040] 1) By adjusting the different combinations of acrylic monomers with methyl side chains and hard monomers with benzene ring structures in the formula, the acrylic monomers with methyl side chains greatly improve the dispersibility of the subsequent coating formula due to the presence of lipophilic methyl groups in the side chains. Since the double bonds under this structure are not easy to rotate, the properties are more stable than acrylic esters. At the same time, the introduction of a rigid benzene ring structure with large steric hindrance can not only weaken the interaction between molecular chains and reduce the viscosity of the polymer, but also give the acrylic resin hardness, dryness, corrosion resistance, etc.
[0041] 2) Improve the existing preparation process, adopt the method of continuous reaction and initiator addition, and control the temperature by heating with medium-temperature heat transfer oil and cooling with cold oil during the reaction process. The monomer conversion rate of the hydroxy acrylic resin finally prepared can reach 99%, and the solid content of the varnish including the resin is about 70%, and the viscosity of the resin is controlled at 1500-3000mPa·s. The hydroxy acrylic resin prepared in this application has excellent operation and construction performance, and the steel structure anticorrosion coating prepared at the same time has excellent adhesion, high hardness and acid and alkali resistance.
[0042] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the present application more clear, the embodiments of the present application will be described in detail below. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.
[0044] The present invention is further described in detail below in conjunction with specific examples, but the examples should not be construed as limiting the present invention. The raw materials of this application are all conventional products on the market.
[0045] Example 1
[0046] A hydroxy acrylic resin is prepared from the following raw materials in percentage by mass: 6.2% of methyl methacrylate, 5% of butyl methacrylate, 20% of butyl acrylate, 11.4% of hydroxyethyl acrylate, 21.3% of styrene, 0.8% of acrylic acid, 2.5% of dibenzoyl peroxide, 21.8% of xylene, and 11% of butyl acetate.
[0047] Among them, in the hydroxy acrylic resin, the mass ratio of the acrylic monomer containing a methyl side chain to the hard monomer containing a benzene ring structure is 1:1.9.
[0048] The preparation method of the hydroxy acrylic resin comprises the following steps:
[0049] Methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and 80% of the initiator dibenzoyl peroxide are sucked into a dropping tank and stirred to obtain a mixture;
[0050] Add 80% of xylene and all butyl acetate into the reactor, raise the temperature to 124±2°C, add the mixture in the dropping tank within 2-2.5 hours, and keep copolymerizing for 1 hour;
[0051] After the reaction was completed, the remaining amount of xylene and dibenzoyl peroxide were added, and the reaction was continued for 2 hours, then the temperature was lowered and the material was discharged.
[0052] The solid content of the prepared hydroxy acrylic resin was detected to be 66.8%, the theoretical solid content was 67%, the conversion rate was 99%, and the resin viscosity was 2317 mPa·s.
[0053] Example 2
[0054] A hydroxy acrylic resin is prepared from the following raw materials in percentage by mass: 5.4% of methyl methacrylate, 4.5% of butyl methacrylate, 20% of butyl acrylate, 11.4% of hydroxyethyl acrylate, 22.7% of styrene, 0.8% of acrylic acid, 2.5% of dibenzoyl peroxide, 21.8% of xylene, and 11% of butyl acetate.
[0055] Among them, in the hydroxy acrylic resin, the mass ratio of the acrylic monomer containing a methyl side chain to the hard monomer containing a benzene ring structure is 1:2.3.
[0056] The preparation method of the hydroxy acrylic resin comprises the following steps:
[0057] Methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and 80% of the initiator dibenzoyl peroxide are sucked into a dropping tank and stirred to obtain a mixture;
[0058] Add 80% of xylene and all butyl acetate into the reactor, raise the temperature to 124±2°C, add the mixture in the dropping tank within 2-2.5 hours, and keep copolymerizing for 1 hour;
[0059] After the reaction was completed, the remaining amount of xylene and dibenzoyl peroxide were added, and the reaction was continued for 2 hours, then the temperature was lowered and the material was discharged.
[0060] The solid content of the prepared hydroxy acrylic resin was detected to be 66.7%, the theoretical solid content was 67%, the conversion rate was 99%, and the resin viscosity was 2074 mPa·s.
[0061] Example 3
[0062] A hydroxy acrylic resin is prepared from the following raw materials in percentage by mass: 4.8% of methyl methacrylate, 4% of butyl methacrylate, 20% of butyl acrylate, 11.4% of hydroxyethyl acrylate, 23.8% of styrene, 0.8% of acrylic acid, 2.5% of dibenzoyl peroxide, 21.8% of xylene and 11% of butyl acetate.
[0063] Among them, in the hydroxy acrylic resin, the mass ratio of the acrylic monomer containing a methyl side chain to the hard monomer containing a benzene ring structure is 1:2.7.
[0064] The preparation method of the hydroxy acrylic resin comprises the following steps:
[0065] Methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and 80% of the initiator dibenzoyl peroxide are sucked into a dropping tank and stirred to obtain a mixture;
[0066] Add 80% of xylene and all butyl acetate into the reactor, raise the temperature to 124±2°C, add the mixture in the dropping tank within 2-2.5 hours, and keep copolymerizing for 1 hour;
[0067] After the reaction was completed, the remaining amount of xylene and dibenzoyl peroxide were added, and the reaction was continued for 2 hours, then the temperature was lowered and the material was discharged.
[0068] The solid content of the prepared hydroxy acrylic resin was detected to be 66.6%, the theoretical solid content was 67%, the conversion rate was 99%, and the resin viscosity was 1766 mPa·s.
[0069] Comparative Example 1
[0070] A hydroxy acrylic resin is prepared from the following raw materials in percentage by mass: 10.4% of methyl methacrylate, 8.7% of butyl methacrylate, 20% of butyl acrylate, 11.4% of hydroxyethyl acrylate, 13.4% of styrene, 0.8% of acrylic acid, 2.5% of dibenzoyl peroxide, 21.8% of xylene and 11% of butyl acetate.
[0071] Among them, in the hydroxy acrylic resin, the mass ratio of the acrylic monomer containing a methyl side chain to the hard monomer containing a benzene ring structure is 1:0.7.
[0072] The preparation method is the same as Example 1.
[0073] The solid content of the prepared hydroxy acrylic resin was detected to be 66.6%, the theoretical solid content was 67%, the conversion rate was 99%, and the resin viscosity was 3714 mPa·s.
[0074] Comparative Example 2
[0075] A hydroxy acrylic resin is prepared from the following raw materials in percentage by mass: 3.1% of methyl methacrylate, 2.5% of butyl methacrylate, 20% of butyl acrylate, 11.4% of hydroxyethyl acrylate, 26.9% of styrene, 0.8% of acrylic acid, 2.5% of dibenzoyl peroxide, 21.8% of xylene, and 11% of butyl acetate.
[0076] Among them, in the hydroxy acrylic resin, the mass ratio of the acrylic monomer containing a methyl side chain to the hard monomer containing a benzene ring structure is 1:4.8.
[0077] The preparation method is the same as Example 1.
[0078] The solid content of the prepared hydroxy acrylic resin was detected to be 66.8%, the theoretical solid content was 67%, the conversion rate was 99%, and the resin viscosity was 1324 mPa·s.
[0079] Comparative Example 3
[0080] Comparative Example 3 is compared with Example 1, without preparing acrylic resin, and a commercially available high-solid and low-viscosity hydroxy acrylic resin from Jiangsu Sanmu is selected for testing, which is marked as Comparative Example 3.
[0081] The solid content was detected to be 65% and the viscosity was 5304 mPa·s.
[0082] test:
[0083] The hydroxy acrylic resins prepared in Examples 1-3 and Comparative Examples 1-3 were tested for their solid content, viscosity, acid value and other performance indicators, wherein the solid content of the resin was tested in accordance with GB / T1725-2007 "Determination of non-volatile content of paints, varnishes and plastics", the viscosity was tested in accordance with GB / T 2404-2008 "Method for determination of viscosity of acrylic resins", the acid value was tested in accordance with GB / T12008.5-2010 "Determination of acid value of plastic polyether polyols", the fineness was tested in accordance with GB / T 1724-1979 "Determination of fineness of coatings", and the color number was tested in accordance with GB / T1722-92 "Determination of color of varnishes, clear oils and thinners". The test results are shown in Table 1.
[0084] Table 1 Performance indexes of high solid and low viscosity hydroxyl acrylic resin of examples and comparative examples
[0085]
[0086] Application Examples
[0087] 1. The hydroxy acrylic resins prepared in the above Examples 1-3 and Comparative Examples 1-3 were used to prepare varnishes according to the formula in Table 2 below.
[0088] The surface drying time of varnish shall be tested according to GB / T 1728-1979 "Determination of drying time of paint film and putty film", the flexibility shall be tested according to GB / T 1731-1993 "Determination of flexibility of paint film", and the hardness shall be tested according to GB / T The adhesion is tested according to GB / T9286-1998 "Scratch test of paint and varnish film", the impact resistance is tested according to GB / T1732-1993 "Determination of impact resistance of paint film", the gloss is tested according to GB / T9754-2007 method, the artificial aging resistance is tested according to GB / T1865-1997 "Artificial weathering and artificial radiation exposure of paints and varnishes" and GB / T1766-1995 "Rating method for aging of paint and varnish coatings", the acid resistance, alkali resistance and salt spray resistance of the resin are formulated into polyurethane coatings and tested according to the relevant testing standards in HG / T2454-2014 "Solvent-based polyurethane coatings (two-component)".
[0089] Table 2 Formulation of acrylic resin industrial varnish
[0090] Raw material name percentage(%) Hydroxylated acrylic resin of Examples 1-3 or Comparative Examples 1-3 79.9% N-75 Curing Agent 19.9% Defoamer BYK-052n 0.1% Dispersant Afcona-5065 0.1%
[0091] 2. Paint film detection
[0092] The prepared varnish was sprayed on the polished tinplate surface with a film thickness of 23±3 μm. The performance was tested after drying. The results are shown in Table 3 below.
[0093] Table 3 Properties of hydroxyl acrylic resin coating
[0094]
[0095]
[0096] The above experimental results show that:
[0097] By adjusting the different combinations of acrylic monomers containing methyl side chains of acrylic resin and hard monomers containing benzene ring structures, especially the ratio of methyl methacrylate, butyl methacrylate, etc. to monomers such as styrene, the results show that when the styrene ratio content increases, due to the larger steric hindrance of the benzene ring, the viscosity of the resin as a whole, as well as the stain resistance and water resistance, are improved. However, after exceeding a certain ratio, the resin rigidity is too strong, and the paint film is prone to brittleness. At the same time, due to the presence of side chain methyl, the Tg of the resin of different chain length acrylic monomers increases significantly, which neutralizes the surface drying time and flexibility of the paint film to a certain extent. By coordinating the ratio of the two types of monomers, while the solid content of the hydroxyl acrylic resin varnish prepared within the scope of this application is relatively high, the resin viscosity is greatly reduced compared with commercially available products, and its construction performance is greatly improved in actual operation. More excellent is that the varnish prepared therefrom has excellent adhesion, high hardness and acid and alkali resistance, and it has achieved a better improvement effect for the deficiencies in the prior art.
[0098] The above-described embodiments are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering and technical personnel in the field shall fall within the protection scope of the claims of the present invention.
Claims
1. A hydroxy acrylic resin, characterized in that The raw materials of the hydroxy acrylic resin are composed of the following by mass percentage: 4%-15% of methyl methacrylate, 3%-12% of butyl methacrylate, 15%-25% of butyl acrylate, 8%-15% of hydroxyethyl acrylate, 15%-25% of styrene, 0.3%-1.0% of acrylic acid, 0.1%-2.5% of initiator, and 21%-40% of organic solvent.
2. The hydroxy acrylic resin according to claim 1, characterized in that The organic solvent is one or a mixture of xylene, toluene, butyl acetate, ethyl acetate, butanone and pentanone; Optionally, the organic solvent is a mixture of xylene and butyl acetate.
3. The hydroxy acrylic resin according to claim 2, characterized in that The raw materials of the hydroxy acrylic resin are composed of the following by mass percentage: 4%-15% of methyl methacrylate, 3%-12% of butyl methacrylate, 15%-25% of butyl acrylate, 8%-15% of hydroxyethyl acrylate, 15%-25% of styrene, 0.3%-1.0% of acrylic acid, 0.1%-2.5% of initiator, 20%-30% of xylene, and 1%-15% of butyl acetate.
4. The hydroxy acrylic resin according to any one of claims 1 to 3, characterized in that The monomer conversion rate of the hydroxy acrylic resin is 99%, the solid content is 66.6%-66.8%, and the viscosity of the resin is controlled at 1500-3000 mPa·s; and / or In the hydroxy acrylic resin, the mass ratio of the acrylic monomer containing a methyl side chain to the hard monomer containing a benzene ring structure is 1:1.4-2.
8.
5. The hydroxy acrylic resin according to any one of claims 1 to 3, characterized in that The initiator is one of azobisisobutyl cyanide, azobisisoheptyl cyanide, dibenzoyl peroxide, cumene hydroperoxide, potassium persulfate, and ammonium persulfate; Optionally, the initiator is dibenzoyl peroxide.
6. A method for preparing the hydroxy acrylic resin according to any one of claims 2 to 3, characterized in that: The following steps are involved: 1) According to the proportion, methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, acrylic acid, and part of the initiator are sucked into a dropping tank and stirred to obtain a mixture; 2) adding part of xylene and all the measured butyl acetate into the reactor as a base and heating it, dripping the mixture in the dropping tank into the reactor, and maintaining copolymerization after the dripping is completed; 3) Add the remaining amount of xylene and initiator, keep warm and then cool down to discharge the material.
7. The method according to claim 6, characterized in that Step 1) comprises: according to the ratio, methyl methacrylate, butyl methacrylate, butyl acrylate, styrene, hydroxyethyl acrylate, and acrylic acid are pumped into a dropping tank, a portion of the initiator is weighed and added into the dropping tank, and stirring is started until it is uniformly dissolved to obtain the mixture; Optionally, the initiator is added in an amount of 80%.
8. The method according to claim 6 or 7, characterized in that: Step 2) comprises: adding 80% of xylene and all of butyl acetate into a reaction kettle to form a bottom and heating it, dripping the mixture in the dripping tank into the reaction kettle, and maintaining copolymerization for 1 hour after the dripping is completed; Optionally, add some xylene and butyl acetate to the reactor apparatus as a base, and raise the temperature to 124±2°C within 1.5 hours and maintain for 10 minutes; Optionally, at 124±2° C. and without reflux, the mixture in the dropping tank is dripped into the reaction kettle within 2-2.5 hours, and the copolymerization is maintained for 1 hour after the dripping is completed.
9. The method according to claim 6 or 7, characterized in that: Step 3) comprises: at 124±2° C., adding the remaining xylene and the initiator mixed solution dropwise into the reactor within 5-10 minutes, maintaining copolymerization for 2 hours, cooling the reactor to 80° C. and discharging the material to obtain the hydroxy acrylic resin. 10 . A hydroxy acrylic resin prepared by the method for preparing a hydroxy acrylic resin according to claim 6 . 11 . A coating, wherein a raw material of the coating comprises the hydroxy acrylic resin according to any one of claims 1 to 5 or a hydroxy acrylic resin prepared by the method for preparing a hydroxy acrylic resin according to any one of claims 6 to 9.
12. A coating formed from the coating material according to claim 11.
Citation Information
Patent Citations
High-solid low-viscosity hydroxy acrylic resin and preparation process thereof
CN101921357A
Hydroxyl acrylic resin and preparation method thereof
CN104231148A
Preparation method of carbon nanotube / polyacrylic acid hydrogel, product and application thereof
LU502100B1